(untitled) (Journal of the College of Education for Women, 2018)
Stream of Consciousness technique has a great impact on writing literary texts in the modern age. This technique was broadly used in the late of nineteen century as a result of thedecay of plot, especially in novel writing. Novelists began to use stream of consciousness technique as a new phenomenon, because it goes deeper into the human mind and soul through involving it in writing. Modern novel has changed after Victorian age from the traditional novel that considers themes of religion, culture, social matters, etc. to be a group of irregular events and thoughts interrogate or reveal the inner feeling of readers. This study simplifies stream of consciousness technique through clarifying the three levels of conscious (Consciousness, Precociousness and Unconsciousness)as well as the subconsciousness, based on Sigmund Freud theory. It also sheds a light on the relationship between stream of consciousness, interior monologue, soliloquy and collective unconscious. Finally, This paper explains the beneficial aspects of the stream of consciousness technique in our daily life. It shows how this technique can releaseour feelings and emotions, as well as free our mind from the pressure of thoughts that are upsetting our mind